A study on Nalidixic Acid Resistant Salmonella among the patients attending Shree Birendra Hospital - Chaudhary, Raina; Sijapati, Khagendra; Singh, Sunil Kumar (Medical Journal of Shree Birendra Hospital, 2012)
Introduction: Enteric fever is the commonest public health problem in developing countries like Nepal. Multi Drug Resistant Salmonella isolates are in vitro susceptible to Quinolone but exhibited a higher Minimum Inhibitory Concentration in vivo. Such phenomenon can be demonstrated by simple disc diffusion test of Nalidixic Acid which shows resistance. This study is conducted to determine prevalence of Nalidixic Acid Resistant Salmonella with their anti biotic sensitivity pattern at Shree Birendra Hospital, Chauni, kathmandu. Method: Of total 3945 blood samples from the patients suspected to have enteric fever were collected during the period of January 2011 to August 2011. Then it was mixed with Brain Heart Infusion , further processed according to standard methodology and their anti microbial susceptibility was performed by Kirby-Bauer disc diffusion method. Results: From 3945 samples, 280 (7.09%) showed positi ve growth, 114 (40.7%) Salmonella enterica serotype Typhi and 166 (59.2%) Salmonella enterica serotype Paratyphi A. a total of 221 (78.92%) were Nalidixic Acid Resistant Salmonella, all these strains were sensitive to Ciprofloxcin and Ofloxacin in disc diffusion test. Conclusion: Study showed a higher frequency of Nalidixic Acid Resistant Salmonella among the patients. screening of Nalidixic Acid disc diffusion test must be done as routine work for determination of low level resistance of Quinolone so as to decide the drug for the treatment of enteric fever. DOI: http://dx.doi.org/10.3126/mjsbh.v10i2.6453 Medical Journal of Shree Birendra Hospital July-Dec 2011 10(2) 1-3